Temporary employment on the basis of civil law contracts – assessment of legal regulation - Walczak, Krzysztof (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
Temporary employment on the basis of civil law contracts raises serious doubts. According to the Author, temporary employment agencies, due to their specificity, should employ only on the basis of labour law contracts. Assigning people to work on the basis of civil law contracts can be carried out only in the mediation formula. Thus, the temporary employment agency becomes the agent of the employed person, and on his behalf sets the terms of the contract. Under this assumption, any statutory restrictions on the terms and conditions of employment constitute a violation of the freedom to conduct a business resulting from the Constitution. This also applies to the need to provide trade unions with information on the conditions under which the cooperation agreement is to be implemented. These regulations make the civil law way of doing work a fiction. On the other hand, employment may be considered a violation of the provisions of the Labour Code.